2008
DOI: 10.1364/oe.16.001945
|View full text |Cite
|
Sign up to set email alerts
|

Fiber strain sensor based on a π-phase-shifted Bragg grating and the Pound-Drever-Hall technique

Abstract: A fiber strain sensor based on a p-phase-shifted Bragg grating and an extended cavity diode laser is proposed. Locking the laser frequency to grating resonance by the Pound-Drever-Hall technique results in a strain power spectral density S(epsilon) (f) = (3 x 10(-19) f(-1) +2.6 x 10(-23)) epsilon(2)/Hz in the Fourier frequency range from 1 kHz to 10 MHz (epsilon being the applied strain), corresponding to a minimum sensitivity of 5 pepsilon Hz(-1/2) for frequencies larger than 100 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
58
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(61 citation statements)
references
References 15 publications
1
58
1
1
Order By: Relevance
“…However, the gain medium only shows small and uncontrollable wavelength dependence, so that the sensitivity is low. Recently, ultrasonic sensors based on π-phase-shifted FBGs (πFBG) have attracted a great deal of attention for highly-sensitive ultrasonic detection [5,[8][9][10]. A πFBG can be conceptually considered as a Fabry-Perot cavity formed by two grating mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the gain medium only shows small and uncontrollable wavelength dependence, so that the sensitivity is low. Recently, ultrasonic sensors based on π-phase-shifted FBGs (πFBG) have attracted a great deal of attention for highly-sensitive ultrasonic detection [5,[8][9][10]. A πFBG can be conceptually considered as a Fabry-Perot cavity formed by two grating mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…A number of high-resolution FBG strain sensors based on complex structures have been developed, including Fabry-Perot configuration [8,9], π-phase shifted gratings [10,11] chirped gratings [12], and sampled structures [13]. For instance, Gagliardi et al demonstrated a strain measurement at the 10 −13 ε·Hz −1/2 scale using an FBG resonator with a diode-laser source which is stabilized against quartz-disciplined optical frequency comb [1]; Huang et al proposed a static-strain sensor with a resolution of 1.0 nε based on a π-phase-shifted Bragg grating, combined with a wavelet threshold denoising algorithm [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-optic ultrasonic sensors based on regular fiber Bragg gratings (FBGs) or π-phaseshifted FBGs have received a great deal of attention in the past decades for their potential applications in structural health monitoring such as ultrasonic testing and acoustic emission (AE) detection [1][2][3][4][5][6][7]. A common demodulation method for these sensors is to use a tunable laser whose wavelength is set within a linear range of the grating spectrum.…”
Section: Introductionmentioning
confidence: 99%